(Un)Making the Insurrectional City: Illicit Infrastructures of Care and Repression in the 2018 Nicaraguan Protests. Issue 3 (21st December 2022) - Díaz, Ricardo; Weegels, Julienne
In this paper, we explore the socio-material infrastructures that maintained and repressed the 2018 Nicaraguan protests, as they made and unmade the insurrectional city. We consider the insurrectional city to be an urban place that is socio-materially reconfigured by the act of revolt and ensuing conflict. In Nicaragua, the insurrectional city (re)emerged as an entangled moral material battleground where past and present practices and notions of insurrection, as well as diverging imaginations for the future collided. With the 2018 protests, new material and human flows settled onto the streets, disrupting extant ways of being in and moving through the city. These were directly deemed illicit by government authorities, who projected the protesters as vandals, thugs, and later even terrorists. A competing ethics of care emerged then, as protesters and (para-)state actors understood the protection and defense of their lives and respective political projects differently. Autoconvocados (self-convened protesters) organized socio-material networks to distribute vital goods for protesters occupying public space, at the same time that the government mobilized its hybrid repressive apparatus to quash and criminalize both the protesters and the care networks supporting their activities. To understand the city-making practices that the protests engendered – both during the months-long insurrection and in its aftermath – examining the interplay between care, repression and legitimacy is crucial.